The activity of the Research Investments in Global Health study and ways forward within the global funding and policy landscape. Issue 8 (November 2016) - Head, Michael; Brown, Rebecca
Abstract The Research Investments in Global Health (ResIn, www.researchinvestments.org ) study analyses funding trends in health research, with a predominant focus on infectious diseases. Since October 2015, the project is funded by the Bill & Melinda Gates Foundation and is now based at the University of Southampton in the UK. In 2016, Public Policy@Southampton provided ResIn with a small grant to explore developing links with policy, funding and research stakeholders with an interest in global health. Three meetings were organised in London (Wellcome Trust, 25 May 2016), Brussels (UK Research Office, 2 June 2016), and Geneva (WHO R&D Observatory, 8 June 2016). In total, 45 stakeholders attended and provided comment and critique on the study methodology and potential expansion into other disciplines. A theme that emerged across all three meetings concerned the use of a standardised categorisation system. A key benefit of the ResIn study is the ability to present granular detail in precise areas. Further work packages that could enhance the use of the collected R&D data included integration with geospatial, policy and scientometric methodologies. There was broad enthusiasm that outputs from these proposed projects would provide clear benefits in informing health policy and R&D strategy. Outputs from the ongoing study covering infection-related R&D investments in the G20 nations will be available in 2017.